Decoding the Chloroplast Genome of Bitterwood (Picrasma quassioides): Structure, Variability, and Evolutionary Relationships - Qin Liu; Huaxi Huang; Jinhang Lin; Fanglin Liu; Xuexue Wang; Rong Chen; Xiaoshan Geng (Ecology and Evolution, 2025)
ABSTRACT The chloroplast genome of Picrasma quassioides, a medicinally significant plant in traditional Asian medicine, was sequenced and analyzed to understand its genetic architecture and evolutionary relationships within Simaroubaceae. High‐throughput sequencing revealed a 160,013‐bp circular genome with a typical quadripartite structure, encoding 132 genes including 87 protein‐coding genes, 37 tRNA genes, and 8 rRNA genes. Comparative analysis with other Simaroubaceae species identified distinct patterns of nucleotide diversity between single‐copy and repeat regions, while examination of IR boundaries revealed dynamic evolutionary processes. Analysis of 101 SSR loci and 48 repeat sequences provided insights into genome organization and potential molecular markers for species identification. Selective pressure analysis across 78 protein‐coding genes demonstrated predominant purifying selection (average Ka/Ks ratio 0.23), with evidence of positive selection in specific genes. Phylogenetic reconstruction using 77 protein‐coding sequences confirmed Simaroubaceae's monophyly and revealed a close evolutionary relationship with Rutaceae. These findings advance our understanding of chloroplast genome evolution within Simaroubaceae while providing molecular tools for authentication and breeding of this valuable medicinal species. The comprehensive genomic characterization establishes a foundation for investigating the genetic basis of therapeutic properties in P. quassioides and facilitating its conservation.